2014
DOI: 10.1093/eurpub/cku086
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting breast cancer treatment delay in Turkey: a study from Turkish Federation of Breast Diseases Societies

Abstract: Background: One of the most important factors in breast cancer (BC) mortality is treatment delay. The primary goal of this survey was to identify factors affecting the total delay time (TDT) in Turkish BC patients. Methods: A total of 1031 patients with BC were surveyed using a uniform questionnaire. The time between discovering the first symptom and signing up for the first medical visit (patient delay time; PDT) and the time between the first medical visit and the start of therapy (system delay time; SDT) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 25 publications
8
44
2
3
Order By: Relevance
“…In this context, the Turkish Ministry of Health declared that all females beginning at the age of 20 years should practice BSE and admitted for clinical breast examination (CBE) (Republic of Turkey, 2008). Although the screening of females aged 40-69 years is free of charge in all cancer control departments, the attendance rates for early diagnose methods are not at expected levels most probably due to the lack of organized nationwide breast health screening program in Turkey (Ozmen et al, 2014). In this case, a BSE on a regular basis has an essential importance in Turkish women lives for the risk of this special disease growing steadily in numbers.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the Turkish Ministry of Health declared that all females beginning at the age of 20 years should practice BSE and admitted for clinical breast examination (CBE) (Republic of Turkey, 2008). Although the screening of females aged 40-69 years is free of charge in all cancer control departments, the attendance rates for early diagnose methods are not at expected levels most probably due to the lack of organized nationwide breast health screening program in Turkey (Ozmen et al, 2014). In this case, a BSE on a regular basis has an essential importance in Turkish women lives for the risk of this special disease growing steadily in numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of stage 0 and I breast cancer are 5% and 27%, respectively, according to the Turkish Federation of Breast Diseases Societies' (Türkiye Meme Hastalıkları Dernekleri Federasyonu-TMHDF) database, which includes more than 22 000 patients (10). There is also a delay in initiating treatment for advanced-stage cancer because of patient and systemrelated factors (12). In our study, which included 1038 patients with breast cancer, the total delay to treatment initiation was 14.8 weeks, most of which was related with the health system (10.5 weeks) (12).…”
Section: Introductionmentioning
confidence: 82%
“…There is also a delay in initiating treatment for advanced-stage cancer because of patient and systemrelated factors (12). In our study, which included 1038 patients with breast cancer, the total delay to treatment initiation was 14.8 weeks, most of which was related with the health system (10.5 weeks) (12).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In our country, where the period from the occurrence of breast cancer symptoms until the beginning of treatment is 14 months, the significance of improving awareness and implementation of populationbased mammography screening programs is apparent (16). The 7-year results of Bahçeşehir Population-Based Mammographic Screening Program showed that screening can be performed in our country; the participation rate was 80% even in the 4th screening period; the rate of patients diagnosed with Stage 0 and I breast cancer was over 70%; and was in accordance with the rates in developed countries.…”
Section: Bahceşehir Population-based Organized Mammography Screening mentioning
confidence: 99%